2009
DOI: 10.1007/s11265-009-0342-7
|View full text |Cite
|
Sign up to set email alerts
|

Video Streaming with Network Coding

Abstract: Recent years have witnessed an explosive growth in multimedia streaming applications over the Internet. Notably, Content Delivery Networks (CDN) and Peer-to-Peer (P2P) networks have emerged as two effective paradigms for delivering multimedia contents over the Internet. One salient feature shared between these two networks is the inherent support for path diversity streaming where a receiver receives multiple streams simultaneously on different network paths as a result of having multiple senders. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
46
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 20 publications
0
46
0
1
Order By: Relevance
“…CDNs spread live or non-live video to users, i.e., before beginning a video streaming session (in a non-live setting), the source server can disperse a video to various assisted servers (Cisco, 2010;Nguyen, Nguyen, & Cheung, 2010). In order to view the video, the user then connects a few of these assisted servers in parallel.…”
Section: Bit Rate Video Streamingmentioning
confidence: 99%
“…CDNs spread live or non-live video to users, i.e., before beginning a video streaming session (in a non-live setting), the source server can disperse a video to various assisted servers (Cisco, 2010;Nguyen, Nguyen, & Cheung, 2010). In order to view the video, the user then connects a few of these assisted servers in parallel.…”
Section: Bit Rate Video Streamingmentioning
confidence: 99%
“…• FEC based UEP Schemes -Packet-level Schemes: as in [1], [59], [60], [62], [63], [67], [69], [71], [74], [78], [85], [87]- [89], [92], [93], [98], [99], [101], mitigate the packet-loss events, as exemplified by the packets lost in Internet-routers [39]. These schemes are typically hard-decoded at the higher layers.…”
Section: Layered Video Communicationsmentioning
confidence: 99%
“…Nguyen et al [89] designed hierarchical network coding (HNC), where the less important bits are used for protecting the more important bits.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent research has focused on using inter-session network coding and demonstrated its potential advantages for high quality streaming media [13], [14].…”
Section: Introductionmentioning
confidence: 99%